Redesigning a Discipline-Specific Writing Assignment to Improve Writing on an EMI Programme of Engineering - Eriksson, Andreas (Journal of Academic Writing, 2018)
English-medium instruction (EMI) in higher education presents challenges at many different levels for educators and students. One of the challenges is disciplinary writing, as students typically study disciplinary content through, and also write in, English as a second or a foreign language. The present, exploratory intervention study uses the redesign of a writing assignment in a Master’s level engineering course at a Swedish university to investigate challenges of disciplinary writing in an EMI context. The study describes how collaboration between content and communication staff helped unpack some of the challenges that students faced. The results show that the students’ texts improved and that the redesign helped them to better adjust to a genre partially new to them. The study also underscores the value for programmes to have a clear plan for writing. The planning is likely to benefit from collaboration between disciplinary and communication faculty, as these participants bring different knowledge to the process.